Cartilage palisades versus temporalis fascia: a randomised control trial - Sarin, Vanita; Shahi, Arpita Chatterjee (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Tympanic membrane perforation is a common cause of hearing loss. Various surgical techniques with different graft materials have been described for the treatment of perforations. The most widely used graft materials are the cartilage and temporalis fascia. Methods: We conducted a prospective randomised control longitudinal study to document the post operative hearing outcomes of type 1 tympanoplasty in patients with inactive mucosal chronic otitis media (n=120) using the cartilage palisades tympanoplasty technique (n=60) and temporalis fascia (n=60). Results: It was found that the mean AB (air-bone) gap at 5 months post operatively was 12.35±7.17 dB with temporalis fascia and 11.39±7.907 dB in cartilage palisades tympanoplasty. At 12 months the AB gap was 14.98±9.915 dB in temporalis fascia group as compared 11.41±8.288 dB for cartilage palisades group. Thus, hearing improvement was better in cartilage palisades group, but interestingly the comparison of the air conduction gain and subjective improvement at the end of 5 and 12 months between the two techniques was not statistically significant and parallels the above findings. Conclusions: Hence we conclude that both temporalis fascia and cartilage palisades were acceptable graft material for successful closure of tympanic membrane perforation.